Penerapan Konsep “Sao Ria” Pada Interior Pusat Informasi Kebudayaan Ende, Flores, Nusa Tenggara Timur - Anastasia Lubalu; Laksmi Kusuma Wardani; Lucky Basuki (Intra, 2019)
Ende is a district in the center of the Flores island. Ende Regency has three main tribes namely Ja'o, Lio and Nga'o who are rich in values, philosophy, customs and culture that interesting to learn. In addition to culture, Ende Regency has natural beauty and a wealth of art and culture. However, the potential and wealth that exists does not yet have complete cultural learning space and facilities.Departing from the potential and problems that exist, the designer formulates the problem, how to design the interior of an Ende cultural information center that is innovative, creative and educative by raising the philosophy concept "Sao Ria" while introducing the traditional Ende-Lio house in its interior.The method used in this design follows the diagram made by Veronique Hillen which consists of 3 main stages , Inspiration, Ideation, and Implementation.The design implementation in this design raised the concept of Sao Ria which is a typical architectural building of Ende lio, and then packaged in a modern way. The facilities provided are galleries area based on seven cultural elements, multipurpose showrooms, auditoriums, music and dance studios, workshops, cafes, souvenir shops and other supporting facilities.